(untitled) (INNOVATIVE ECONOMY, 2025)
Vavrynets V.Ya. INNOVATIVE DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN THE CURRENT ENVIRONMENT Purpose. The aim of the study is to analyse the theoretical foundations and practical aspects of innovative development of enterprises in the context of modern challenges, with an emphasis on the integration of digitalization and the application of artificial intelligence as key drivers of competitiveness and sustainable development. Methodology of research. The article uses a systematic approach, general and special research methods, in particular: methods of comparative analysis, content analysis of recent publications and research in the field of innovative development of enterprises, in particular the application of artificial intelligence; deduction and induction – to formulate scientific hypotheses, laws and principles; formal-logical – for theoretical generalizations, justification of the research methodology, and formulation of conclusions; monographic – for researching the content of innovative enterprise development; the method of analysis and synthesis, which allowed for the systematization of scientific approaches to innovative enterprise development. Findings. The necessity of intensifying innovative activity of enterprises as the only effective way of economic development in modern conditions is substantiated. The study found that innovation is a key driver of modern enterprise development, contributing to the transformation of technological, organizational, and management processes. It was proved that innovative activity encompasses not only the introduction of new products and technologies, but also profound changes in the structure of thinking, corporate culture, and organizational interaction within the enterprise. An assessment of investments in artificial intelligence was carried out. It was analysed that in the context of rapid changes in the global market, digitalization, and increased competition, the innovative capacity of an enterprise determines its competitiveness and adaptability. Particular attention was paid to the role of artificial intelligence as a strategic resource within Industry 4.0. It was concluded that its integration into management and production processes significantly increases efficiency and opens up new opportunities for sustainable development and market growth. Originality. It was proved that the integration of artificial intelligence into the innovative development of an enterprise, unlike existing approaches, makes it possible to radically rethink strategic goals and business processes, ensuring increased efficiency and competitiveness in the context of digitalization. It was established that generative artificial intelligence models are a powerful tool for optimizing business processes, which, unlike traditional methods, allows for the processing of large data sets with greater speed and accuracy, opening up new opportunities for innovation in manufacturing, finance, and the public sector. It was substantiated that a model of innovative enterprise development that combines strategic adaptation and systemic renewal with digital transformation and technology integration (including the Internet of Things and big data analytics), unlike existing models, will enable the creation of a flexible and sustainable innovation ecosystem. The understanding of the role of artificial intelligence as a multidisciplinary catalyst that transforms not only production but also management, logistics, and marketing processes, contributing to the formation of new business opportunities, has been further developed. Practical value. The proposed approach to organizing innovative development of enterprises will enable them to comprehensively integrate innovative technologies, optimize business processes, and quickly adapt to changes in the external environment, such as increased competition and technological trends. Key words: innovation, innovative development of the enterprise, digitalization, business process, artificial intelligence.